A new genus of lime treefrogs (Anura: Hylidae: Sphaenorhynchini) - Araujo-Vieira, Katyuscia; Luna, Maria Celeste; Caramaschi, Ulisses; Haddad, Célio F.B. [UNESP] (Elsevier, 2020)
The hylid tribe Sphaenorhynchini is composed of the single genus Sphaenorhynchus. A recent total evidence phylogenetic analysis of all the 15 currently described species of Sphaenorhynchus recovered S. pauloalvini as the earliest diverging taxon of this genus. Sphaenorhynchus pauloalvini is diagnosed by molecular evidence and several phenotypic characters that differentiate it from the remaining species of Sphaenorhynchus. On the basis of molecular evidence and an extensive list of phenotypic characters, we erect a new monotypic genus for S. pauloalvini and redefine the former Sphaenorhynchus to include the remaining species of this genus.
Keywords: Atlantic forest; Genus description; Hylinae; Morphology; Synapomorphies; Taxonomy